OPTIMALISASI PENJUALAN SUPLEMEN PADA PT. MERCK INDONESIA - Nuhung, Mahmud (Perpustakaan dan Penerbitan Unismuh Makassar, 2013)
Research aims to explain the factors that influence theoptimization of the sales, as well as analyzing sales volume growthsupplements on PT Merck Indonesia. collected data are secondary data,such as cost of promotion, distribution channels, pricing, and value ofsales. hypothesis testing using multiple regression. The results showedthat simultaneous promotion costs, distribution costs, and the cost ofgoods sold have a significant effect on the increase in value sales of PTMerck Indonesia and promotion costs are partially dominant variableinfluence on the increase in value of sales at PT Merck Indonesia